Enterprise Architecture for Education: A TOGAF Approach to Achieve Digital Transformation and Optimal Performance (A Case Study of Shared Service Function) - Febrianto, Prima; Fajrillah, Asti Amalia Nur; Febriyani, Widia (Syntax Corporation, 2024)
In today's fast-paced digital world, educational institutions must keep up with technological advancements to stay competitive and effective. This study focuses on designing Enterprise Architecture (EA) for an educational foundation, specifically its Shared Service Department, using the TOGAF ADM 9.2 framework. The aim is to enhance the foundation's IT cybersecurity maturity as part of its digital transformation efforts. Through a detailed analysis, challenges such as inadequate business process mapping, documentation procedures, human resource management, and information system organization were identified, highlighting the need for systematic IT governance and architecture. The research culminates in a tailored EA blueprint covering areas like business processes, data management, and applications. This blueprint acts as a strategic guide for improving operations, optimizing resources, and fostering innovation within the foundation. By integrating existing applications and developing targeted solutions, the design aims to enhance service delivery and move the foundation towards international educational excellence standards. The findings emphasize the importance of continuous adaptation to evolving technology and the need for ongoing refinement in areas like infrastructure and migration planning. Overall, this research provides valuable insights and practical Enterprise blueprint recommendations for improving operational efficiency and achieving strategic goals in today's digitalized educational landscape.